an ANALYSIS ON THE INFLUENCE OF SELF-EFFICACY, PROFESSIONAL TDEVELOPMENT, UNDERSTANDING RISK-BASED INTERNAL AUDIT ON AUDIT QUALITY WITH ORGANIZATIONAL COMMITMENT AS MODERATING VARIABLE AT THE INSPECTORATE OF NORTH SUMATERA PROVINCE - gaol, masria lumban (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to find out 1) the influence of Self-Efficacy, Professional Development, and Understanding Risk-Based Internal Audit on Audit Quality at the Inspectorate of North Sumatera Province, and 2) Organizational Commitment in modernizing the influence of Self-Efficacy, Professional Development, and Understanding Risk-Based Internal Audit at the Inspectorate of North Sumatera Province, The population used causality method. The population was 85 APIPs (Government Internal Controllers) at the Inspectorate of North Sumatera Province, and all of them were used as the samples (total population/census sampling). Primary data were gathered by using survey technique by distributing questionnaires to all respondents and analyzed by using measurement model (outer model) and structural model (inner model), and effect size for moderating variable. The result of the research showed that 1) Self-Efficacy, Professional Development, and Understanding Risk-Based Internal Audit on Audit Quality had positive and significant influence on Audit Quality at the Inspectorate of North Sumatera Province, and 2) Organizational Commitment could moderate the influence of Understanding Risk-Based Internal Audit on Audit on Audit Quality at the Inspectorate of North Sumatera Province.